1989
DOI: 10.2466/pr0.1989.64.3.851
|View full text |Cite
|
Sign up to set email alerts
|

Sense of Humor as a Mediator during Incidental Learning of Humor-Related Material

Abstract: Variations in attention during intentional or incidental learning were investigated. Materials for intentional learning were presented to 165 college students in conjunction with peripheral cues of humorous and non-humorous materials presented for incidental learning. An hypothesized funneling effect, an attentional shift during learning to the incidental materials, was not found for humorous or non-humorous materials and intentional recall of materials. Subjects with high self-reported sense of humor attended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Humor also has an impact on learning. Dixon et al (1989) found that individuals who are high in humor pay more attention when learning humorous material and also recall it better. Therefore, humor functions as an important precursor to psychological safety and leads to more learning.…”
Section: Psychological Safety and Learningmentioning
confidence: 97%
“…Humor also has an impact on learning. Dixon et al (1989) found that individuals who are high in humor pay more attention when learning humorous material and also recall it better. Therefore, humor functions as an important precursor to psychological safety and leads to more learning.…”
Section: Psychological Safety and Learningmentioning
confidence: 97%
“…showing that humor in general can increase learning (Bolkan & Goodboy, 2015;Dixon, et al, 1989;Kaplan & Pascoe, 1977;Wanzer & Frymier, 1999;Wanzer, et al, 2010;Ziv, 1988) in that Study 1 showed higher overall learning rates than the original Trust studies (Koenig & Harris, 2005). A study directly comparing humorous and non-humorous conditions would be necessary to determine whether this is the case.…”
Section: Humor and Trustmentioning
confidence: 94%
“…The literature on humor and learning is varied in its results. For instance, while humor in the classroom can increase test scores or perceived cognitive learning in higher education, the humor must be related to the content, be positive in nature, and perhaps even be conceptual (Bolkan & Goodboy, 2015;Dixon, Willingham, Strano, & Chandler, 1989;Kaplan & Pascoe, 1977;Wanzer & Frymier, 1999;Wanzer, Frymier, & Irwin, 2010;Ziv, 1988). And even when these criteria are fulfilled, sometimes humor decreases test scores (Fisher, 1997).…”
mentioning
confidence: 99%
“…Many studies have been conducted on the use of humor in learning, such as the role of humor in physics learning (Berge, 2017), the use of verbal humor to build the closeness of the teacher with his students (Gorham & Christophel, 1990), students' perceptions of humor used in learning (Melissa B. Wanzer, Frymier, & Irwin, 2010;Melissa Bekelja Wanzer & Frymier, 1999), humor used as a problem-based learning facility (Chauvet & Hofmeyer, 2007), the relationship between humor and intelligence, creativity, and (Hauck & Thomas, 1972) learning, and the use of humor in other learning activities (Dixon, Strano, Willingham, & Chandler, 2011;Fisher, 1997;Mihalcea & Strapparava, 2006;Shively, 2013;Wu, 2008;Ziv, 1988). This research, I hope to be able to add references for researchers and teachers, especially Indonesian subjects, which can be used as suggestions in the teaching and learning process.…”
Section: "A Policeman An Army and An Intel"mentioning
confidence: 99%